Physiologically relevant microsystems to study viral infection in the human liver - McDuffie, Dennis; Barr, David; Agarwal, Ashutosh; Thomas, Emmanuel (Frontiers in Microbiology, 2022)
Viral hepatitis is a leading cause of liver disease and mortality. Infection can occur acutely or chronically, but the mechanisms that govern the clearance of virus or lack thereof are poorly understood and merit further investigation. Though cures for viral hepatitis have been developed, they are expensive, not readily accessible in vulnerable populations and some patients may remain at an increased risk of developing hepatocellular carcinoma even after viral clearance. To sustain infection in vitro, hepatocytes must be fully mature and remain in a differentiated state. However, primary hepatocytes rapidly dedifferentiate in conventional 2D in vitro platforms. Physiologically relevant or physiomimetic microsystems, are increasingly popular alternatives to traditional two-dimensional (2D) monocultures for in vitro studies. Physiomimetic systems reconstruct and incorporate elements of the native cellular microenvironment to improve biologic functionality in vitro. Multiple elements contribute to these models including ancillary tissue architecture, cell co-cultures, matrix proteins, chemical gradients and mechanical forces that contribute to increased viability, longevity and physiologic function for the tissue of interest. These microsystems are used in a wide variety of applications to study biological phenomena. Here, we explore the use of physiomimetic microsystems as tools for studying viral hepatitis infection in the liver and how the design of these platforms is tailored for enhanced investigation of the viral lifecycle when compared to conventional 2D cell culture models. Although liver-based physiomimetic microsystems are typically applied in the context of drug studies, the platforms developed for drug discovery purposes offer a solid foundation to support studies on viral hepatitis. Physiomimetic platforms may help prolong hepatocyte functionality in order to sustain chronic viral hepatitis infection in vitro for studying virus-host interactions for prolonged periods.